Concerns about the use of polygenic embryo screening for psychiatric and cognitive traits: personal view - Lencz, Todd; Sabatello, Maya; Docherty, Anna; Peterson, Roseann E; Soda, Takahiro; Austin, Jehannine; Bierut, Laura; Crepaz-Keay, David; Curtis, David; Degenhardt, Franziska; Huckins, Laura; Lazaro-Munoz, Gabriel; et al. (The lancet. Psychiatry, 2022)
Private companies have begun offering services to allow parents undergoing in-vitro fertilisation to screen embryos for genetic risk of complex diseases, including psychiatric disorders. This procedure, called polygenic embryo screening, raises several difficult scientific and ethical issues, as discussed in this Personal View. Polygenic embryo screening depends on the statistical properties of polygenic risk scores, which are complex and not well studied in the context of this proposed clinical application. The clinical, social, and ethical implications of polygenic embryo screening have barely been discussed among relevant stakeholders. To our knowledge, the International Society of Psychiatric Genetics is the first professional biomedical organisation to issue a statement regarding polygenic embryo screening. For the reasons discussed in this Personal View, the Society urges caution and calls for additional research and oversight on the use of polygenic embryo screening.
Online verfügbar: 2. August 2022, Artikelversion: 15. September 2022
Gesehen am 24.09.2024